2022
DOI: 10.3390/polym14122474
|View full text |Cite
|
Sign up to set email alerts
|

Friction Stir Welding Optimization of 3D-Printed Acrylonitrile Butadiene Styrene in Hybrid Additive Manufacturing

Abstract: The feasibility of joining material extrusion (MEX) 3D-printed acrylonitrile butadiene styrene (ABS) plates with the friction stir welding (FSW) process was investigated herein as a promising topic of hybrid additive manufacturing (HAM). The influence of three process parameters on the mechanical strength of the joints was thoroughly examined and analyzed with a full factorial experimental design and statistical modeling. Hereto, the welding tool pin geometry, travel speed, and rotational speed were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 51 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…Mechanical tests have shown effective enhancements in the tensile and flexural strengths of both nano- and micro-composite materials [ 51 ]. ABS has also been investigated in Hybrid Additive Manufacturing, combining MEX 3D printing and friction stir welding for manufacturing large parts [ 52 ], or MEX 3D printing and laser cutting for the improvement of the quality characteristics of the parts built with the process [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical tests have shown effective enhancements in the tensile and flexural strengths of both nano- and micro-composite materials [ 51 ]. ABS has also been investigated in Hybrid Additive Manufacturing, combining MEX 3D printing and friction stir welding for manufacturing large parts [ 52 ], or MEX 3D printing and laser cutting for the improvement of the quality characteristics of the parts built with the process [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the pins with increased edges and a triangular shape demonstrated more pronounced heat generation, influencing the heat flux on polyethylene surfaces. Vidakis et al [10] examined the welding tool geometry, rotational speed, and travel speed for acrylonitrile butadiene styrene (ABS) fabricated with a material extrusion process [11]. Ma et al [12] investigated the impact of temperature on the mechanical characteristics of aluminum alloy joints via friction stir welding.…”
Section: Introductionmentioning
confidence: 99%
“…Research is aiming to reduce the effects of these parameters on the quality of the 3D-printed parts by optimizing the 3D printing settings used [ 26 ]. At the same time, MEX 3D printing is combined with other manufacturing techniques in a hybrid additive manufacturing system to further increase the quality of the built parts [ 27 ] and expand the potential fields of application [ 28 ].…”
Section: Introductionmentioning
confidence: 99%